O OURO VERDE DO SEMIÁRIDO: PALMA FORRAGEIRA CONHECIMENTOS E UTILIDADES - Sousa, Luci Cleide Farias Soares; Sousa, José da Silva; Pereira, Emmanuel Moreira; Pereira Filho, Raimundo Raniêr; Borges, Maria da Gloria Borba; Silva, Rosilene Agra da (Caderno Verde de Agroecologia e Desenvolvimento Sustentável, 2013)
_